Doing the Right Thing - Geoffrey C. Hazard Jr. (Washington University Law Quarterly, 1992)
At one level, it is easy to describe the ethical standards observed by many lawyers. Quite bluntly, they are terrible. On the other hand, the ethical standards observed by many lawyers are excellent, particularly considering the very difficult and delicate ethical problems with which they must deal. The problem of "bad actors" in the profession is, in my opinion, primarily the weakness of institutions' ability to secure compliance with the profession's official standards. For example, the disciplinary machinery in many jurisdictions has simply been overwhelmed with grievances that cannot be adequately investigated. However, the focus of the present analysis is not on bad lawyers, but on good lawyers. The central question is whether the nature of legal practice itself, even when conducted with faithful adherence to official standards, is somehow inherently evil. Much criticism of lawyers' ethics is pitched at this level. The essence of this criticism is that lawyers engage, as a vocation, in practices that no moral person would undertake in any circumstance.
Keywords: Legal ethics